PEMBELAJARAN KIMIA BERBASIS KOOPERATIF THINK PAIR SHARE (TPS) DENGAN BERBANTUAN VIRTUAL LABORATORIUM UNTUK MENINGKATKAN HASIL BELAJAR SISWA (Jurnal Inovasi Pendidikan Kimia, 2021)
Element Chemistry is one of the materials given to class XII students. Studying the chemical elements of the substance cause a sense of saturation because of the broad scope of the material and is memorized. To help and facilitate students learning in an effort to understand the material including the Chemical Element material, the use of learning media was developed. This research was conducted with the aim to find out the increase in student learning outcomes through virtual laboratories. The research design used was one group pretest-posttest design. The learning model used is TPS (Think Pair Share) cooperative laboratory assisted with virtual laboratories. The research method used is the test method. The instruments used were pretest and posttest sheets. The results of data analysis using n-gain indicate that an increase in student learning outcomes in the medium and high categories. A total of 66.67% of students experienced an increase in learning outcomes in the medium category, and 33.33% of students experienced an increase in learning outcomes in the high category. From the results obtained, it can be concluded that the virtual laboratory with TPS learning model can significantly improve student learning outcomes.